LEARNING MANAGEMENT THROUGH METACOGNITIVE STRATEGIES TO ENHANCE ENGLISH READING COMPREHENSION SKILLS OF FOURTH-GRADE STUDENTS - Charoen, Pawarisa; Seabsom, Korawan; Saripa, Aree (Journal of MCU Nakhondhat, 2024)
The purposes of this research were: 1) To compare English reading comprehension before and after learning using metacognitive strategies among fourth-grade students, and 2) To examine fourth-grade students’ satisfaction with learning management using metacognitive strategies to enhance English reading comprehension. This research is a quasi-experimental research. The sample consisted of 24 fourth-grade students in the second semester of the 2023 academic year at Bankokchang School, selected via cluster random sampling with the school as the random unit. The research instruments included: 1) Lesson plans for English reading focusing on the main idea using metacognitive strategies, 2) A multiple choice test on English reading comprehension, and 3) A student satisfaction questionnaire on learning management through metacognitive strategies to improve English reading comprehension. Statistical analyses included percentage, mean, standard deviation, and dependent t-test. The results revealed that: 1) English reading comprehension among fourth-grade students significantly improved after learning with metacognitive strategies at the .01 level, and 2) Fourth grade students reported the highest satisfaction levels with learning management using metacognitive strategies to develop English reading comprehension.